The Post-Human Lyric: Diffractive Vision and the Ethics of Mattering in Adam Dickinson’s Anatomic - Ambroży, Paulina (Studia Anglica Posnaniensia, 2020)
The aim of my inquiry is to discuss Adam Dickinson’s revisionist approach to the lyric autobiography as shown in his most recent volume Anatomic (2018a). Informed by an eco-critical sensibility, the biotechnological gaze, and post-humanist notions of subjectivity, this highly experimental conceptual project reveals porous boundaries of the autobiographical self caught up in the entanglement of the mind and matter. Based on burden tests of the poet’s own bodily fluids, Anatomic offers a philosophical speculation on the nature of the human, asking us to go beyond anthropocentric positioning of the subject and to consider ethical alongside onto-epistemological implications of this new direction. The methodology employed in my analyses of Dickinson’s poems derives from the influential notions of agential realism, diffractive vision, and intra-action formulated by Karan Barad – a trained quantum physicist and feminist philosopher working in the field of science and technology. Barad’s theories fuel New Materialist paradigms of thought as they propose the inherent indeterminacy of matter as well as question the established views of identity and the social. The particular focus of my interrogations will be the relationship between diffractive perception and the medical gaze used by the Canadian conceptualist to see himself non-anthropologically and thus to destabilize the perimeters of the autobiographical self.